Digestive physiology of spiny lobsters: implications for formulated diet development. (21st June 2014) - Perera, Erick; Simon, Cedric
Abstract: The development of cost‐effective and nutritionally adequate formulated feeds is a key step for developing sustainable technologies for new aquaculture species. There has been many research effort for over 30 years on feed development for spiny lobsters, but amazingly, poor performance of formulated feeds remains one of the major obstacles to progressing commercial aquaculture of these crustaceans. This is partially due to a lack of information on how spiny lobsters digest and assimilate formulated feeds. The aim of this review is to integrate recent information on the digestive physiology of spiny lobsters to identify areas where further studies are needed for advancing to more physiologically tailored formulated feeds. Increasing the efficiency of mechanical and chemical digestion is imperative for better digestion of formulated feeds. This is likely to be achieved by improving feed format, reducing the particle size of ingredients, using digestible binders, preprocessing or selecting more soluble macronutrients and supplementing feeds with additives such as pH buffers, emulsifying agents and/or exogenous enzymes. Future research needs to adopt a holistic approach for investigating the digestive processes in spiny lobsters by focusing on digestion as well as downstream processes. The protein‐sparing effect of lipids and carbohydrates on spiny lobster metabolism is of a particular significance as the spiny lobster metabolism is strongly directed towards the use of protein. This review provides important insights, practical solutions and key research directions to improve both our understanding of spiny lobster digestive physiology and the performance of formulated feeds for spiny lobsters.